2019
DOI: 10.3390/toxins11060348
|View full text |Cite
|
Sign up to set email alerts
|

Toxin B Variants from Clostridium difficile Strains VPI 10463 and NAP1/027 Share Similar Substrate Profile and Cellular Intoxication Kinetics but Use Different Host Cell Entry Factors

Abstract: Clostridium difficile induces antibiotic-associated diarrhea due to the release of toxin A (TcdA) and toxin B (TcdB), the latter being its main virulence factor. The epidemic strain NAP1/027 has an increased virulence attributed to different factors. We compared cellular intoxication by TcdBNAP1 with that by the reference strain VPI 10463 (TcdBVPI). In a mouse ligated intestinal loop model, TcdBNAP1 induced higher neutrophil recruitment, cytokine release, and epithelial damage than TcdBVPI. Both toxins modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Strikingly, examination of the key residues for TcdB-FZD2 interaction identified in a crystal structure of the VPI10463 TcdB delivery domain bound to the FZD2 cysteine-rich domain (CRD) (57) revealed that many of the TcdB contact residues are not conserved in the RT027 TcdB sequence from C. difficile M7404 (Fig. 3 A, i), confirming recent observations regarding TcdB sequence variations in binding regions (26). A phylogenic analysis of TcdB from annotated RT027 strains deposited onto the National Center for Biotechnology Information (NCBI) database revealed a complete clonal conservation of TcdB within RT027 strains, suggesting that these differences exist for all RT027 strains (SI Appendix, Fig.…”
Section: Rt027 Tcdb Induces Stem Cell Damage In a Frizzled Independensupporting
confidence: 82%
See 1 more Smart Citation
“…Strikingly, examination of the key residues for TcdB-FZD2 interaction identified in a crystal structure of the VPI10463 TcdB delivery domain bound to the FZD2 cysteine-rich domain (CRD) (57) revealed that many of the TcdB contact residues are not conserved in the RT027 TcdB sequence from C. difficile M7404 (Fig. 3 A, i), confirming recent observations regarding TcdB sequence variations in binding regions (26). A phylogenic analysis of TcdB from annotated RT027 strains deposited onto the National Center for Biotechnology Information (NCBI) database revealed a complete clonal conservation of TcdB within RT027 strains, suggesting that these differences exist for all RT027 strains (SI Appendix, Fig.…”
Section: Rt027 Tcdb Induces Stem Cell Damage In a Frizzled Independensupporting
confidence: 82%
“…S1A). Interestingly, infection with the prototypical C. difficile strain 630 (23,24), the pathogenicity locus (PaLoc) of which has 99% sequence identity to VPI10463 PaLoc (25)(26)(27), and strain AI35, a naturally occurring TcdA − TcdB + CDT + strain which encodes a variant TcdB (28), as well as strain JGS6133, a RT078 animal isolate (28), was unable to induce damage beyond the surface of the colonic epithelium ( Fig. 1A) and correlated with 100% survival and recovery from infection similar to CD133, a nontoxigenic clinical isolate (SI Appendix, Fig.…”
Section: Significancementioning
confidence: 99%
“…The classical TcdB (TcdB1) uses chondroitin sulfate proteoglycan 4 36 , poliovirus receptor-like 3 37 , and frizzled proteins (FZDs) 38 as cellular receptors; and can glucosylate small GTPase such as RhoA/B/C, Rac1, Cdc42, TC10, TCL, RhoG, Rap, and Ras [39][40][41] . Recent studies showed that TcdB2 only weakly bound to FZDs when compared with TcdB1 32,42 , likely owing to discrepancies between FZD-binding sequences of TcdB1 and TcdB2 43,44 . Also, when compared with TcdB1, both TcdB3 and TcdB4 showed a drastically reduced ability to glucosylate RhoA and Cdc42 15,23 , which was also supported by our sequence analyses (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, strains such as R20291 (belonging to RT027) produces a TcdB variant with ~8% of residue differences from the reference TcdB, which exhibited a significant impact on its immunogenicity: mice immunized with the reference TcdB developed resistance to the same TcdB, but all died when challenged with this variant TcdB 34 , and several antibodies raised against the reference TcdB, including the FDA approved therapeutic antibody bezlotoxumab, either do not recognize or have lower efficacy against this TcdB variant [34][35][36] . Furthermore, this TcdB variant also loses the ability to recognize frizzled (FZD) proteins, which are one of the major receptors for the reference TcdB, due to residue changes at the FZD-binding interface 35,[37][38][39][40] .…”
Section: Introductionmentioning
confidence: 99%